SOCIAL STUDIES COMIC: APPLICATION OF NEUROPEDAGOGY APPROACH TO SOCIAL STUDIES TEXT BOOK OF SMP KELAS VII - Supriatna, Nana; Fauzi, Wildan Insan; Holilah, Mina (Universitas Pendidikan Indonesia, 2019)
Research on brain based learning began intensive since the 1990s and mostly revolves around the teaching and learning process. The abundance of research on neuorsains has a profound effect on the speed of brain-based learning research. Meanwhile, research on history textbooks mostly takes the theme of historiography and minimal research on its use in learning. This is where the importance of research is brain based learning and social studies textbooks. Textbook research related to brain-based learning has been initiated by the team since 2013. This year's research, researchers will conduct further research on brain-based learning as the basis for making IPS comic textbooks. Based on the study of previous research findings, the application of Neuropedagogy in IPS textbooks in the form of comics includes: time line, a glimpse of info, historical lessons, behind characters, mind maps, historical caricatures, historical humor, historical mysteries, contemporary issues, if history, and memorizing strategies . The main limitation of this research problem is how is the application of brain-based learning in social studies text books VII class? This research uses a research and development approach model with the steps in this process referring to the form of a cycle.